1993
DOI: 10.1002/jmri.1880030417
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging of knee hyaline cartilage: Evaluation of two‐ and three‐dimensional sequences

Abstract: Magnetic resonance (MR) imaging of cadaveric knees was performed to determine optimal sequences for visualization of hyaline cartilage. Full-thickness cartilage lesions ranging in diameter from 1 to 5 mm and a partial-thickness cartilage lesion 15 mm in diameter were created in the femoral articular surfaces of three cadaveric knees. The knees were then imaged with a 1.5-T imager with various two-dimensional and high-resolution three-dimensional (3D) techniques. After imaging, the knee specimens were sectioned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
1
3

Year Published

1996
1996
2003
2003

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 14 publications
2
22
1
3
Order By: Relevance
“…Disler et al [4] optimized the contrast-to-noise ratio of knee cartilage to saline for a fat-saturated 3D SPGR sequence and found similar sequence parameters (60/5, 40 ° flip angle) to be best. Tervonen et al [6] also found 3D SPGR (30/9, 30 ° flip angle) to be superior to 3D GRASS and steady stat e free precession (SSFP) techniques in the detection of cartilage lesions created in human cadaver knees. Van der Linden [10] deemed a SPGR sequence (65/11.5; 30o-45 ° flip angle) preferable to other spoiled and steady-state GRE sequences at 0.5 T in the depiction of lesions created in pig cartilage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Disler et al [4] optimized the contrast-to-noise ratio of knee cartilage to saline for a fat-saturated 3D SPGR sequence and found similar sequence parameters (60/5, 40 ° flip angle) to be best. Tervonen et al [6] also found 3D SPGR (30/9, 30 ° flip angle) to be superior to 3D GRASS and steady stat e free precession (SSFP) techniques in the detection of cartilage lesions created in human cadaver knees. Van der Linden [10] deemed a SPGR sequence (65/11.5; 30o-45 ° flip angle) preferable to other spoiled and steady-state GRE sequences at 0.5 T in the depiction of lesions created in pig cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…We used a dark fluid sequence for 3D saline imaging, whereas a bright fluid sequence was used for 3D gadolinium-enhanced imaging. Our choice of MR pulse sequences was based on prevailing recommendations in the literature [4][5][6] and on our o w n clinical experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcified cartilage makes up to 10% of the total cartilage thickness [1,16]. With this in mind, the limiting factor is not the calcified tissue, which is difficult to delineate by MRI in commonly used sequences [21], but the resolution in plane.…”
Section: Discussionmentioning
confidence: 99%
“…So far there has been no clear consensus on which technique is best for cartilage imaging. Three-dimensional sequences [21] with thin slices [15] provide better results in the assessment of hyaline cartilage thickness and hyaline cartilage volume. Fat-suppressed sequences may improve the discrimination of cartilage [20,21].…”
Section: Discussionmentioning
confidence: 99%